Simplify both sides of the equation
-5/2 x +3/4 x = -3/4
Combine like terms
(-5/2 x + 3/4 x )
-7/4 x = -3/4
-7/4 x = -3/4
Multiply both sides by 4/(-7)
(4/-7)*(-7/4 x ) = (4/-7 ) * ( -3/4 )
x = 3/7
Answer:
A
Step-by-step explanation:
First 4 sets of (x, y) show that when x increases 2, y increases 3. It seems the relationship is linear. But last 2 set show that x increases 1, y increases 3. So the relation is NOT linear
=−640x10+1280x9+19904x8−40728x7−144488x6+323904x5−162304x4+1024x3+2048x2
step by step
(2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x(x+4)
=((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(x+4)
=((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(x)+((2x+8x2+3x−4x(x−4)(x−1)(20)x+4)(2)(x+4)(x−4)(2)x(x−1)(2)x)(4)
=−640x10+3840x9+4544x8−58904x7+91128x6−40608x5+128x4+512x3−2560x9+15360x8+18176x7−235616x6+364512x5−162432x4+512x3+2048x2
=−640x10+1280x9+19904x8−40728x7−144488x6+323904x5−162304x4+1024x3+2048x2